Phase diagram of YbZnGaO4 in applied magnetic field - William Steinhardt (Nature Portfolio, 2021)
Abstract Recently, Yb-based triangular-lattice antiferromagnets have garnered significant interest as possible quantum spin-liquid candidates. One example is YbMgGaO4, which showed many promising spin-liquid features, but also possesses a high degree of disorder owing to site-mixing between the non-magnetic cations. To further elucidate the role of chemical disorder and to explore the phase diagram of these materials in applied field, we present neutron scattering and sensitive magnetometry measurements of the closely related compound, YbZnGaO4. Our results suggest a difference in magnetic anisotropy between the two compounds, and we use key observations of the magnetic phase crossover to motivate an exploration of the field- and exchange parameter-dependent phase diagram, providing an expanded view of the available magnetic states in applied field. This enriched map of the phase space serves as a basis to restrict the values of parameters describing the magnetic Hamiltonian with broad application to recently discovered related materials.